Outcome of expectantly managed small-for-gestational-age pregnancies with normal Doppler parameters- a prospective cohort study - Mishra, Sneha; Agarwal, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: SGA foetuses with normal Dopplers are not at risk of IUD. However, there is lack of consensus about timing of delivery of SGA foetuses. Clinicians commonly induce all SGA pregnancies at 37 weeks. Expectant management of SGA foetuses beyond 37 weeks is not well studied. Methods: We followed up women with clinically suspected growth restriction with foetal biometry, Doppler and biophysical profile. Pregnancies with foetal AC between 10th to 3rd centile with normal Dopplers were recruited in the study group. The women were allowed to go in spontaneous labor till 39+6/7 weeks or were induced at 39+6/7 weeks. The outcome of such cases was compared with controls who were induced at 37+0/7 weeks. Results: Spontaneous labor occurred in 42% subjects in study group whereas in control group all were induced. Mean gestation at delivery in the study group was increased (39.57±0.71 versus 37.0±0.0, p value <0.001). Almost 81% of the subjects in study group delivered after 39 weeks. The rate of caesarean section was significantly lower in study group (3% versus 22%, p value-0.024). Also, the risk of intrapartum foetal distress was lower in study group (3/36 versus 1/36).The mean birth weight in the study group was higher (2426.5±154.1 gm versus 2297.9±101.4 gm, p value <0.001. Conclusions: Expectant management of SGA pregnancies with normal Doppler parameters leads to a significant increase in gestational age at birth and the mean birth weight and a significant reduction in caesarean section rate.